A bicycle vendor on Baker Lane in Mazagaon - Mumbai Archive Project Team (Jio Institute, 2024)
A bicycle vendor on Baker Lane, which links Hospital Lane and D'Lima Street. As the name implies, Baker Lane was home to numerous bakeries that provided dock workers with freshly made pao. The workforce was made up of people from many communities, regions, and faiths. Each group had its eating traditions, but there was one food that they all shared: the locally made bread, or pao.